2021
DOI: 10.1177/15330338211065877
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of VAV Gene Family Predicts Poor Prognosis of Acute Myeloid Leukemia

Abstract: Objectives: VAV family genes ( VAV1, VAV2, and VAV3) are associated with prognosis in various cancers; however, they have not been evaluated in acute myeloid leukemia (AML). In this study, the prognostic value of VAV expression in AML was evaluated by a single-center study in combination with bioinformatics analyses. Methods: The expression and prognostic value of VAVs in patients with AML were investigated using various databases, including GEPIA, CCLE, EMBL-EBI, UALCAN, cBioPortal, STRING, and DAVID. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The review focused here on the involvement of Vav1 in hematopoietic malignancies, especially T cell malignancies. High expression of Vav1 was shown to predict a poor prognosis of acute myeloid leukemia (AML) [104]. Also, numerous studies reported missense/deletion mutations (Figure 2A) and fusions/translocations (Figure 2B) in Vav1 in T cell lymphoma (TCL) [105][106][107][108][109].…”
Section: Vav1 and Cancermentioning
confidence: 98%
“…The review focused here on the involvement of Vav1 in hematopoietic malignancies, especially T cell malignancies. High expression of Vav1 was shown to predict a poor prognosis of acute myeloid leukemia (AML) [104]. Also, numerous studies reported missense/deletion mutations (Figure 2A) and fusions/translocations (Figure 2B) in Vav1 in T cell lymphoma (TCL) [105][106][107][108][109].…”
Section: Vav1 and Cancermentioning
confidence: 98%
“…VAV1 overexpression in hematopoietic malignancies-VAV1 has also been shown to be deregulated in hematologic malignancies [21,[64][65][66]. Thus, it was detected as overexpressed in 13% of B-cell non-Hodgkin Lymphoma (B-NHL) and 34•4% of B-cell chronic lymphocytic leukemia (B-CLL) [64].…”
Section: Vav1 Ectopic Expression In Human Tumorsmentioning
confidence: 99%
“…VAV1 overexpression was also associated with activation and higher proliferative activity of diffuse large B-cell lymphoma (DLBCL) [65]. VAV1 expression was also significantly higher in acute myeloid leukemia (AML) patients than in control tissues [66]. Those AML patients with high VAV1 expression were less likely to achieve complete remission compared to those patients with low VAV1 expression, thus suggesting that VAV1 expression levels have prognostic value [66].…”
Section: Vav1 Ectopic Expression In Human Tumorsmentioning
confidence: 99%